Temporary Retention in Cold Water Reduces Postrelease Behavioral Impairment in Angled Rainbow Trout. (13th January 2022) - Chhor, Auston D.; Reid, Jessica L.; Holder, Peter E.; Nowell, Liane B.; Brownscombe, Jacob W.; Danylchuk, Andy J.; Cooke, Steven J.
Abstract: The effectiveness of catch and release as a conservation practice assumes minimal impacts to released fish. In most cases, angling‐related stressors can be mitigated via changes to angler behavior that reduce fight duration, handling, and air exposure. In some cases, stressors may significantly impact the ability of fish to engage in normal swimming behavior upon release. In these scenarios, it may be beneficial for anglers to assist recovery or retain fish until they are adequately recovered. We investigated the effectiveness of two assisted‐recovery devices at facilitating behavioral recovery in angled Rainbow Trout Oncorhynchus mykiss : (1) retention in a flow box, or (2) retention in a water‐filled cooler. Additionally, we compared the effects of assisted recovery in surface water (24–27°C) or cool water pumped from the hypolimnion (17–19°C). From July to mid‐September 2020, 169 fish were angled from five stocked lakes at Kenauk Nature (Montebello, Quebec). Fish were air exposed for 30 s, for 15 s, or not at all (0 s) and were held in a flow box or a water‐filled cooler for 3 min, while fish in a control group were immediately released. Triaxial acceleration and temperature biologgers were temporarily fixed around the trunk of the fish with Velcro to observe postrelease swimming behavior for 10 min. Rainbow Trout that were held in assisted‐recovery devices regained equilibrium significantly more quickly than those that were immediately released, and fish that were held in 17–19°C water regained equilibrium the most rapidly. In fish that were air exposed for 30 s, individuals that were held in recovery devices exhibited greater swimming activity compared to those that were immediately released. Our study demonstrates that for Rainbow Trout, assisted‐recovery devices can reduce equilibrium impairment, especially when water in the recovery devices is significantly cooler than the relatively warm surface water temperature. Global water temperatures are expected to rise as a result of anthropogenic climate change, and best practices for angling should be adapted to reflect increased thermal stressors for many game fish species. Ensuring that fish are vigorous upon release is imperative for reducing postrelease mortality caused by predation or thermal stress.